Cross Sectional Study to Evaluate the Reason for Removal of LARC Contraception - Shahid, Aisha; Shah, Nighat Ali; Kashaf, Memoona; Riyaz, Asma; Sattar, Ayesha; Sheerin (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of various reasons for removal of long-acting reversible contraception (LARC) among women of reproductive age presenting at a tertiary care hospital. Methodology: This cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Jinnah Postgraduate Medical Centre (JPMC) from March, 2025 to May, 2025 and Reproductive Health Services Center, Population Welfare Department (PWD), Karachi. A total of 143 women aged 15–45 years who were using LARC and planned to have it removed were included through non-probability consecutive sampling. A self-designed proforma was used to document demographic details and reasons for LARC removal. Data were analyzed using SPSS version 20. Frequencies and percentages were calculated, and stratification was done based on education, residence, and socioeconomic status. Results: Out of 143 participants, the most common reason for LARC removal was completion of the contraceptive period (44.0%), followed by desire to conceive (21.0%) and opting for another method (17.5%). Husband disapproval was reported in 8.4% of cases. Irregular per vaginal bleeding and lower abdominal pain were noted in 5.6% and 3.5% of cases, respectively. Conclusion: Most women discontinued LARC for planned or non-medical reasons, indicating a positive trend in contraceptive utilization. However, factors such as spousal disapproval and mild physical complaints contributed to early removal. Strengthening counseling, involving partners in family planning, and managing minor side effects can improve LARC continuation rates and overall reproductive health outcomes.